Corpus-assisted CDA of George Floyd’s Murder Reports on CNN and Aljazeera - Putri, Radya Cantika Suhardiman; Mardiah, Zaqiatul (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
In 2020, one news that shook the world was the murder of an Afro-American named George Floyd by Minneapolis police officers. This study focuses on the media coverage of George Floyd’s murder case by two news outlets, CNN and Aljazeera. We used a Corpus-assisted Critical Discourse Analysis (CACDA) technique to compare how each news outlet portrayed the social actors involved in the incident and to identify if any social actors were excluded from the reporting, eventually revealing which side each media was inclined to. The analysis was based on Theo Van Leeuwen’s theory and utilized the Antconc application. The data used in this study consists of ten news articles, five from CNN and Aljazeera, published between May and July 2020. A literature study was conducted to collect the data. The Antconc corpus-processing application was then used to process the large amount of data collected, enabling quick, extensive, and comprehensive analysis. We uploaded all ten articles to the Antconc application and used the frequency feature to identify the five most used words in the ten news articles. The top five words were further analyzed using van Leeuwen’s critical discourse analysis, excluding irrelevant particles. The result shows that CNN aligned with the police and Aljazeera aligned with Floyd. By the ideological stances of CNN and Aljazeera, readers can become more aware of potential biases in news articles concerning George Floyd’s murder.